2013
DOI: 10.1111/icad.12026
|View full text |Cite
|
Sign up to set email alerts
|

Nesting site density and distribution affect Osmia lignaria (Hymenoptera: Megachilidae) reproductive success and almond yield in a commercial orchard

Abstract: 1. The potential of commercially managed, native blue orchard bees, Osmia lignaria, to augment honey bees in orchard pollination depends on various factors, particularly how to enhance O. lignaria retention while optimising even pollination throughout orchards by varying their stocking density and nesting site distribution.2. In 2011, we investigated how artificial nest box density and the number of cavities within nest boxes influenced O. lignaria retention and reproduction in a 61 ha almond orchard pollinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…Different authors have demonstrated that Bombus terrestris is an effective pollinator of raspberries and tomatoes (Ahmad et al, ; Willmer, Bataw, & Hughes, ). Regarding mason bees, different studies have focused on the efficiency of mason bees, such as Osmia cornuta (Márquez, Bosch, & Vicens, ; Monzón, Bosch, & Retana, ; Vicens & Bosch, ) and Osmia lignaria ( Artz, Allan, Wardell, & Pitts‐Singer, ; Boyle & Pitts‐Singer, ; Koh, Lonsdorf, Artz, Pitts‐Singer, & Ricketts, ) . The potential competition between different species of bumble bees ( Bombus vosnesenskii and Bombus melanopygus) and mason bees ( O. lignaria ) with the honey bee has been examined in at least one study, carried out in California by Brittain, Williams, Kremen, and Klein () in an almond orchard; these authors found no evidence of competition but rather an enhancement of the pollination activity of A. mellifera .…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have demonstrated that Bombus terrestris is an effective pollinator of raspberries and tomatoes (Ahmad et al, ; Willmer, Bataw, & Hughes, ). Regarding mason bees, different studies have focused on the efficiency of mason bees, such as Osmia cornuta (Márquez, Bosch, & Vicens, ; Monzón, Bosch, & Retana, ; Vicens & Bosch, ) and Osmia lignaria ( Artz, Allan, Wardell, & Pitts‐Singer, ; Boyle & Pitts‐Singer, ; Koh, Lonsdorf, Artz, Pitts‐Singer, & Ricketts, ) . The potential competition between different species of bumble bees ( Bombus vosnesenskii and Bombus melanopygus) and mason bees ( O. lignaria ) with the honey bee has been examined in at least one study, carried out in California by Brittain, Williams, Kremen, and Klein () in an almond orchard; these authors found no evidence of competition but rather an enhancement of the pollination activity of A. mellifera .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, almond orchards are planned and managed to improve relative fruit set by planting pollinizer rows on either side of the main cultivar rows to increase availability of compatible pollen (Dag et al 2000). The use of bees in almond orchards during flowering increases the likelihood of movement of pollen among trees (Artz et al 2013;Brittain et al 2013). Enhancing tree nutrition has also been reported to increase fruit set rates (Nyomora et al 1997(Nyomora et al , 1999.…”
mentioning
confidence: 99%
“…Since the bees require some incubation to emerge, time can be lost by emerging them in the orchard, so releasing emerged bees (like the "bleed-off" in alfalfa leafcutting bees) has been tried successfully in almonds (M. Allan and S. Peterson, unpublished data). Additionally, offering many smaller nest sites improves establishment compared to fewer sites per unit of area (Torchio, 1984b;Artz et al, 2013). Recent work showed that nest box density and the number of cavities within nest boxes influenced blue orchard bee retention in almonds (Artz et al, 2013).…”
Section: The Blue Orchard Beementioning
confidence: 99%
“…Additionally, offering many smaller nest sites improves establishment compared to fewer sites per unit of area (Torchio, 1984b;Artz et al, 2013). Recent work showed that nest box density and the number of cavities within nest boxes influenced blue orchard bee retention in almonds (Artz et al, 2013). Females completed more nests in high-density, low-cavity nest boxes compared to low-density, high-cavity nest boxes.…”
Section: The Blue Orchard Beementioning
confidence: 99%